The Influence of Viral Marketing and Brand Awareness on Consumers Purchase Intention of Mixue Beverage Products in Jakarta - Nursalim, Haris (AIBPM Publisher, 2023)
Nowadays, the development of the beverage industry has progressed very rapidly which encourages beverage business entrepreneurs to create innovative products to meet the changing needs of society, namely boba drinks or bubble tea. Competition in the beverage industry makes companies compete to attract the attention of consumers to buy the products they sell, one of which is an ice cream and tea company, Mixue, by promoting its brands and products through social media. The theories in this study are viral marketing, brand awareness, and purchase intent. The variables in this study are divided into two types, namely independent and dependent variables. The independent variables in this research are viral marketing and brand awareness, while the dependent variables in this study are purchase intent. The object of the study is Mixue beverage products. Data collection was carried out by distributing questionnaires to 102 samples of male and female consumers who were at least 17 years old and above and had seen Mixue viral ads on Instagram or TikTok. Then, this research data were processed using SPSS 25 using non-probability sampling with judgment sampling technique. The results of this study are viral marketing and brand awareness have proven to have a positive significant effect on consumers purchase intention of Mixue beverage products in JakartaÂ Keywords: Beverage Products, Brand Awareness, Mixue, Purchase Intention, Viral Marketing